E. coli Plasmid Vectors Methods and Applications - Casali, Nicola; Preston, Andrew; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2003)
Manipulation of recombinant DNA, which is almost exclusively performed using the host E. coli, constitutes one of the fundamental methodologies of molecular biotechnology. In E. coli Plasmid Vectors, experienced bench researchers describe their proven techniques for the manipulation of recombinant plasmids utilizing this popular bacterial host. The authors describe readily reproducible methods for cloning DNA into plasmid vectors, transforming plasmids into E. coli, and analyzing recombinant clones. They also include protocols for the construction and screening of libraries, as well as specific techniques for specialized cloning vehicles, such as cosmids, bacterial artificial chromosomes, l vectors, and phagemids. Also presented are methods for common downstream applications, such as mutagenesis, expression of recombinant proteins and RNA transcripts, and uses of reporter genes. Each fully tested protocol is described in step-by-step detail by an established expert in the field and includes an introduction outlining the principles behind the technique, lists of the necessary equipment and reagents, tips on troubleshooting and avoiding known pitfalls and, where needed, a discussion of the interpretation and use of the results. Comprehensive and highly practical, E. coli Plasmid Vectors offers those new to the field a basic guide to the use of plasmid vectors in the cloning host E. coli, and those more experienced researchers a broad-ranging, proven array of successful techniques.
The Function and Organization of Plasmids -- Choosing a Cloning Vector -- Escherichia coli Host Strains -- Chemical Transformation of E. coli -- Electroporation of E. coli -- DNA Transfer by Bacterial Conjugation -- Cosmid Packaging and Infection of E. coli -- Isolation of Plasmids from E. coli by Alkaline Lysis -- Isolation of Plasmids from E. coli by Boiling Lysis -- High-Purity Plasmid Isolation Using Silica Oxide -- High-Throughput Plasmid Extraction Using Microtiter Plates -- Isolation of Cosmid and BAC DNA from E. coli -- Preparation of Single-Stranded DNA from Phagemid Vectors -- Using Desktop Cloning Software to Plan, Track, and Evaluate Cloning Projects -- Cloning in Plasmid Vectors -- Extraction of DNA from Agarose Gels -- Cloning PCR Products with T-Vectors -- Construction of Genomic Libraries in ?-Vectors -- Rapid Screening of Recombinant Plasmids -- Restriction Analysis of Recombinant Plasmids -- Screening Recombinant DNA Libraries -- Sequencing Using Fluorescent-Labeled Nucleotides -- Site-Directed Mutagenesis Using the Megaprimer Method -- Site-Directed Mutagenesis by Inverse PCR -- Creating Nested DNA Deletions Using Exonuclease III -- Transposon and Transposome Mutagenesis of Plasmids, Cosmids, and BACs -- In Vitro Transcription and Translation -- Vectors for the Expression of Recombinant Proteins in E. coli -- Expression of Recombinant Proteins From lac Promoters -- Plasmid-Based Reporter Genes -- Plasmid-Based Reporter Genes.
Keywords: Biochemistry; Cell biology; Biochemistry, general; Cell Biology